Modelación con diferencias finitas del comportamiento dinámico de suelos estratificados sometidos a cargas en superficie: Caso 2D (2018)
Whenever an engineering project is conceived, the first thing that must be understood is that it must be linked to the soil through a soil-foundation system, and that the correct interaction between the soil and the foundation must guarantee geotechnical and structural stability of the project. Because the machines and mechanical equipment that generate vibrations are part of the various production systems in the energy industry, mining, steel, oil, etc., it is very common for engineers to find the need to design the foundation for this type of equipment, which is why the adequate knowledge of the behavior of the machine-foundation-soil system is fundamental. Because of the above this project analyzes the behavior of a vibratory machine-foundation-soil system, for a soil of two strata and a foundation of infinite length. The present project is developed by means of the method of finite differences in the time domain (FDTD, for its acronym in English), through a program written in the FORTRAN 90 language using the free platform INTEL VISUAL STUDIO. A model is proposed that contains the static loads of the foundation and dynamics loads of the vibratory machine, in addition to the geometry of the foundation and soil parameters.